Costs Associated with the Treatment of Low Back Disorders: A Comparison of Surgeons and Physiatrists. Issue 6 (18th December 2019) - Standaert, Christopher J.; Li, Justin W.; Glassman, Stuart J.; Manolov, Nikolay E.; Thomas, Santhosh A.; Lee, Anthony A.; Dolak, Melanie A.; Stinneford, M. Kate
Abstract : Background: Spine care is costly and subject to wide variability. Defining costs and patterns of care for different specialties is critical to improving value. Objective: Determine costs, utilization, and differences therein for nonoperative and operative specialists in treating low back disorders. We hypothesized costs associated with nonoperative specialists would be lower. Design: Retrospective cohort. Setting: Medicare Limited Data Set (5% sample), 2011 to 2014. Participants: A total of 170 011 patients saw a primary care provider for a low back disorder between 1 July 2011, and 1 January 2013. Excluding those seen for a low back disorder in the preceding 6 months, final cohorts totaled 11 829 patients subsequently evaluated by a physiatrist (specialist in physical medicine and rehabilitation; 3183 patients) or surgeon (orthopedic or neurosurgeon; 8646 patients) within the following 6 months. Main Outcome Measures: Total Medicare expenditures, spine‐specific costs, spine surgical rates over 24 months. Results: Cohorts had comparable demographics, initial diagnoses, and baseline mean per‐member per‐month (PMPM) total spending. Mean 2‐year spine‐specific spending was 3978 for the physiatrist cohort and 7387 for the surgeon cohort. Comparatively, the physiatrist cohort had lower total mean 2‐year spine‐specific spending (−3409; 95% confidence interval [CI] −3824 to −2994), mean PMPM total spending (−122/mo; CI −184 to −60), and surgical rate (7.8% vs. 18.9%, risk ratio [RR] = 0.41; CI 0.36‐0.47). Surgery predominantly drove cost differential. Mean PMPM total spending for both cohorts remained elevated at 24 months compared to baseline mean spending (physiatrist: +293; CI 447 to 138; surgeon: +325; CI 425 to 225). Conclusions: Following a new episode of a low back disorder, substantial costs were seen for those subsequently evaluated by a physiatrist or surgeon. Costs were considerably lower for those first seen by a physiatrist. Patients in both cohorts displayed long‐term increases in health care costs. Our data suggest that early engagement in nonoperative care, when appropriate, may improve value.